Comparative evaluation of effect of laser on shear bond strength of ceramic bonded with two base metal alloys: An in-vitro study - K Deepak; S C Ahila; B Muthukumar; M Vasanthkumar (Wolters Kluwer Medknow Publications, 2013)
The most common clinical failure in metal ceramic restoration is at the ceramo-metal interface. For the clinical longevity, metal-ceramic prostheses must have satisfactory bond strength between metal and ceramic. Aim and Objective: The aim of this study is to evaluate the effect of Laser etching on shear bond strength between base metal alloys and ceramic. Materials and Methods: A total of 60 specimens were made (Base 5 mm diameter and 1 mm thickness, step with 4 mm diameter and 4 mm in length). They were divided into three groups. Group A-control, Group B-sand blasting, and Group C-laser etching. The Surface morphology, surface roughness, and wettability of the specimens were observed under scanning electron microscope (SEM) Ceramic application was carried out layer by layer for an optimal height of 4 mm. The shear bond strength test was performed using a universal testing machine and the nature of the fracture was examined under SEM. Results: The mean shear bond strength values for laser etched (Group C) Nickel-chromium (Ni-Cr) alloy bonded with ceramic was (49.12 ± 7.12 MPa) and ceramic bonded with Cobalt-chromium (Co-Cr) was (50.04 ± 4.27 MPa), sand blasted (Group B) Ni-Cr alloy bonded with ceramic was (26.00 ± 5.22 MPa), and ceramic bonded with Co-Cr was 24.54 ± 4.78 MPa. The SEM image after debonding showed 10% of adhesive failure and 70% cohesive failure and 20% of both adhesive and cohesive failure for Laser etching. However, there was no significant difference in the values of shear bond strength between the two base metal alloys in Group C. Conclusion: The s hear bond strength between ceramic bonded with Ni-Cr alloys using the Laser etching as surface treatment was 49.12 ± 7.12 MPa and for Co-Cr alloys 50.04 ± 4.27 MPa. Laser surface treatment produces an excellent surface roughness and achieved good shear bond strength values and aid in achieving a better bond strength between metals and ceramic.